Between Sovereignty and Universal Norms: An English School Analysis of Global Responses to Russia’s Anti-LGBT Policies - -, Cepi Novia Tristantri; Hafid Adim Pradana (Universitas Airlangga, 2024)
Since President Vladimir Putin enacted anti-LGBT laws in July 2023, Russia has received a variety of responses, especially those focusing on human rights issues. However, there are quite a few parties who have criticized Russia’s policies. This study aims to understand the differences in global responses to Russia’s anti-LGBT policies, using the English School perspective. This article uses a qualitative descriptive method. Data collection was carried out through literature studies, which came from Scopus journal articles, official Russian government documents, and credible media reports. Using the pluralism and solidarity approaches contained in the English School, the findings in this article can be summarized in two main premises. First, if based on the pluralism approach, the decision of countries that choose not to condemn Russia’s anti LGBT policies can be understood as a form of respect for Russia’s sovereignty in an effort to maintain international order. Second, by using a solidarity approach, the opposition of some pro-LGBT countries and international organizations to Russia’s anti-LGBT policies can be understood as an effort to uphold universal values in order to create international order. Keywords: Anti-LGBT; English School; Pluralism; Russia; Solidarism.